PENGARUH SURAT HIMBAUAN TERHADAP KEPATUHAN WAJIB PAJAK DENGAN KESADARAN SEBAGAI VARIABEL INTERVENING (Studi Kasus Pada KPP Pratama Kebumen) - Dias Candrika Atmayuliana (JURNAL EKOBIS DEWANTARA, 2018)
ABTRACT Taxes as one of the spearheads of the largest source of state revenues and required the participation of the community in fulfilling the obligations in the field of taxation embodied with self assessment system. Government efforts to increase state revenues through taxes must be balanced with good service to the community. This study aims to examine the effect of the appeal letter on taxpayer compliance through taxpayer awareness. To test the hypothesis, used primary data with purposive sampling method, with 95 respondents. Technique of data analysis using path analysis with letter appeal as variable (X) and awareness as intervening variable and taxpayer obedience as variable (Y). After the data in the analysis, it was found that the appeal letter positively affects the consciousness has a t-value of 11.497> t-table value of 3.10 with a significant value of 0.000. Awareness positively affects the taxpayer compliance has a t-value of 4.528> t-table value of 3.10 with a significant value of 0.000. Letter of appeal have a positive effect on taxpayer compliance has a t-value of 6.564> t-table value of 3.10 with a significant value of 0.000. Variable letter appeal to taxpayer compliance 0,563 and indirect influence of 0,504 this result indicate that appeal letter have positive effect to taxpayer compliance through awareness.